Novel Biomarkers For Cancer Diagnosis And Therapeutic Targeting: Insights From Multi-Cancer Studies - Rajan, Keerthy; Sruthy G (Jurnal Vokasi Kesehatan, 2024)
In this systematic review, newly identified biomarkers involve different types of cancer. Their roles are not only analysed but also their applicability in diagnostics, prognosis, and therapy. Examples of such biomarkers would be: SLC35A3 in colorectal cancer, EPYC in pancreatic carcinoma, and ANKRD1 in multiple cancers suggest high potential for the enhancement of diagnosis and treatment in cancer. For instance, with CRC patients, SLC35A3 has poor survival rates, and in pancreatic cancer, EPYC is associated with cancer progression through the PI3K-AKT pathway. SLC35A3, EPYC exist as potential and new immune-related biomarkers in colorectal cancer, including B7H4, the IFN-γ/B7H4 axis, which may have contributions to better future outcomes of immunotherapy by targeting immune evasion mechanisms. For instance, the cross-cancer biomarkers ATP6AP1 and SIGLEC-15 have been discovered, and, indeed, have more therapeutic implications across so many cancer types. In this review, the findings from multi-cancer studies have been integrated to demonstrate the potential of such cross-disciplinary biomarkers in personalized medicine as part of improved patient care outcomes.